Students’ acceptance of and intention to use learning management systems using extended TAM - Eraslan Yalçın, Müyesser. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
The aim of this study is to examine students’ acceptance of and intention to use learning management systems for university education in Turkey using extended Technology Acceptance Model (e-TAM) that allows to find the dominant reason(s)/ factor(s) for learners when using a system. According to literature review, the factors are determined as Behavioral Intention to Use (BIU), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Perceived Interaction (PI), Social Norm (SN), Compatibility with Preferred Work Style (CPWS), User Interface Design (UID), Computer Self-Efficacy (CSE), and Previous Online Learning Experience (POLE). To measure the effects of these factors, a questionnaire, composed of two parts: the items of demographic information and the items of variables, is distributed both by online and by hand. The study is conducted at two different places: Istanbul Bilgi University (56.73%) and Boğaziçi University (43.26%). The total sample of the study is 282. 43.3% of the participants are female and 56.7% of them are male. The data that was collected from the questionnaires were transferred to Excel and then transferred to Statistical Package for Social Sciences (SPSS) Version 20 and SPSS Amos 23 for SEM analysis. The results show that BIU is affected from PU, PEOU, and SN, PU is affected from PEOU, SN, UID, and finally PEOU is affected from UID and CSE.
Keywords: Learning, Method of.